Development Of Fiber Optic Practicum Learning Media Based On Virtual Reality - Saputra, Dimas; Mohammad Fadhli; Martinus Mujur Rose (BEST, 2026)
The rapid development of multimedia technology has encouraged innovation in learning media, particularly for practical-based courses. Fiber optic practicum learning requires direct practice, specialized equipment, and adequate laboratory facilities, which often become constraints, especially during distance learning conditions. This final project aims to develop a virtual reality–based learning media for fiber optic practicum to support students’ understanding of practical procedures in a more interactive and immersive manner.The development process utilizes Blender as a 3D modeling and animation tool to design laboratory environments and fiber optic practicum equipment, including stripper, cleaver, fusion splicer, optical power meter, and fiber optic cables. Verge3D is used to create interactive animations and integrate the models into a virtual reality environment. The learning media simulates key practicum stages, such as cable stripping, cutting, splicing, and attenuation measurement using an optical power meter.The resulting virtual reality learning media allows users to experience fiber optic practicum activities in a simulated laboratory environment as if performing real practices. This media is expected to function as an alternative learning tool that enhances students’ understanding, motivation, and readiness before conducting actual fiber optic practicum in the lab.